A Review of Biomaterials Based on High-Entropy Alloys - Thiago Gonçalves de Oliveira; Danilo Valim Fagundes; Patrícia Capellato; Daniela Sachs; Antonio Augusto Araújo Pinto da Silva (Metals, 2022)
Due to its great amount of microstructure and property possibilities as well as its high thermodynamic stability and superior mechanical performance, the new class of material known as high-entropy alloys (HEAs) has aroused great interest in the research community over the last two decades. Recent works have investigated the potential for applying this material in several strategical conditions such as high temperature structural devices, hydrogen storage, and biological environments. Concerning the biomedical field, several papers have been recently published with the aim of overcoming the limitations of conventional alloys, such as corrosion, fracture, incompatibility with bone tissue, and bacterial infection. Due to the low number of available literature reviews, the aim of the present work is to consolidate the information related to high-entropy alloys developed for biomedical applications (bioHEAs), mainly focused on their microstructure, mechanical performance, and biocompatibility. Topics such as phases, microstructure, constituent elements, and their effect on microstructure and biocompatibility, hardness, elastic modulus, polarization resistance, and corrosion potential are presented and discussed. The works indicate that HEAs have high potential to act as candidates for complementing the materials available for biomedical applications.